Managing conflicting 'Truth Claims' – ambiguity in the diplomat's toolkit in East-Asian Island conflict. Issue 4 (7th August 2016) - Kopper, Akos
Abstract: The article is a study of managing interstate relations via ambiguity and secrecy. At the focal point of the article is the different constitutive logic of domestic politics and diplomacy in conceiving and managing social reality; with the former implying the notion of community and the latter separateness – the difference that allows for diplomatic conduct to rely on tacit agreements and ambiguity for managing contradictory 'truth claims', as China and Japan did in the case of the Ryukyu and later the Senkaku Islands. Such successful management is conditional on the parties' ability to control domestic narratives avoiding contradictions in their 'truth claims' becoming too blatant. Yet, modern technologies increasingly undermine states' capacities for this. The leaking on YouTube of the collision of a Chinese trawler with the ship of the Japanese Coast Guard in 2010 offers a perfect example. The incident aggravated the conflict and triggered intense debates on secrecy in Japan. The article concludes by arguing that once ambiguity and tacit agreements break down, leaders should turn to their public – recognize that noisy nationalist are frequently but a minority – and attempt to renegotiate 'truth claims' domestically to create the basis for a compromise.